2010
DOI: 10.1007/s10705-010-9353-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomass ashes and their phosphorus fertilizing effect on different crops

Abstract: The reutilization of biomass ashes in agriculture is an important issue to create nutrient cycles and to save fertilizer. To analyse the P fertilization effect of crop biomass ashes (rape meal ash (RMA), straw ash (SA), and cereal ash (CA)) in interaction with different crops, two pot experiments with a poor loamy sand deficient in P were carried out. Besides the three ash treatments, other treatments included triple superphosphate (TSP) as a high soluble P source, potassium chloride (KCl) as a high soluble K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 45 publications
(47 reference statements)
7
54
2
1
Order By: Relevance
“…Suspensions of 0.5 g of biomass ash were put into contact with 50 mL of 0.1 M NaNO 3 solutions with different pH values (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), adjusted with HNO 3 and NaOH. The suspensions were agitated for 8 h in a shaker at 350 rpm until an equilibrium pH value was reached.…”
Section: Point Of Zero Charge Of Biomass Ashmentioning
confidence: 99%
“…Suspensions of 0.5 g of biomass ash were put into contact with 50 mL of 0.1 M NaNO 3 solutions with different pH values (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), adjusted with HNO 3 and NaOH. The suspensions were agitated for 8 h in a shaker at 350 rpm until an equilibrium pH value was reached.…”
Section: Point Of Zero Charge Of Biomass Ashmentioning
confidence: 99%
“…Secondly, soil nutrient availability is determined by a combination of three factors: (i) nutrient addition from the ash; (ii) shifts in pH-dependent soil chemical equilibria; and (iii) the extent of change in soil microbial activity. Thus, CFA and wood ash do not seem to be optimal sources of plant available P, particularly when compared with biomass ash (Schiemenz and Eichler-Lobermann, 2010).…”
Section: Elemental Composition Of Cfamentioning
confidence: 94%
“…However, P in CFA is often in forms that are not readily plant available (Page et al, 1979;Adriano et al, 1980;Jala and Goyal, 2006). In comparison with CFA, biomass ash contains high concentrations of P that range from 0.01% in bagasse ash (Jamil et al, 2004) to 10.4% in cereal biomass ash (Eichler et al, 2008;Schiemenz and Eichler-Lobermann, 2010;Schiemenz et al, 2011). Schiemenz et al (2011) reported that the water soluble P in biomass ash is low; however, about 80% of P is soluble in citric acid, which is potentially bioavailable.…”
Section: Elemental Composition Of Cfamentioning
confidence: 99%
See 2 more Smart Citations